TINJAUAN KRITIS TERHADAP KECENDERUNGAN HISTORIOGRAFI INDONESIA MASA KINI - Subekti, Slamet (Faculty of Humanities, Diponegoro University, 2012)
Exercise about Indonesian historiography is interesting, actually to see direction among historian works. As we have seen through library study that modern Indonesian historiography developed by academic historian became Indonesia-centric historiography circa late 1970s. But it’s disappointed, because failed to respond our problems, such as: how history contributes to an effort for overcome socio-political constrain our nation? Today, more historians aware for need to developing alternative historiography, it benefits for nation enlightenment and respond to future challenges. Keywords: historiography, liberation historiography